2010
DOI: 10.1007/s11605-009-1074-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Obstructed Colorectal Malignancy in an Asian Population: Predictors of Morbidity and Comparison Between Left- and Right-Sided Cancers

Abstract: In an Asian population, surgery in patients with acute colorectal malignant obstruction is associated with significant morbidity and mortality rates. Though left-sided malignant obstruction occurs more frequently and is associated with a higher incidence of stoma creation, primary resection and anastomosis is a safe option in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
35
5
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 37 publications
(55 reference statements)
7
35
5
10
Order By: Relevance
“…[7] Intraluminal fecal loading and the difference between the proximal and distal colon diameters renders difficulty in terms of anastomosis technique in patients treated by resection and primary anastomosis. [26,27] An increased incidence of anastomosis leak, which is the most significant disadvantage, has currently been reported within 1-7% in several studies, and the mortality rate has been reported to be 2-9%. [25] In our clinic, we prefer to perform a colostomy in patients with resection and anastomosis in order to lower the morbidity and mortality rates related with anastomosis leakage.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[7] Intraluminal fecal loading and the difference between the proximal and distal colon diameters renders difficulty in terms of anastomosis technique in patients treated by resection and primary anastomosis. [26,27] An increased incidence of anastomosis leak, which is the most significant disadvantage, has currently been reported within 1-7% in several studies, and the mortality rate has been reported to be 2-9%. [25] In our clinic, we prefer to perform a colostomy in patients with resection and anastomosis in order to lower the morbidity and mortality rates related with anastomosis leakage.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies comparing two-step procedures requiring colostomy and resection plus primary anastomosis have demonstrated that length of hospital stay was longer, morbidity was higher, and survival was lower in the two-step procedures. [27] Another treatment alternative in obstructive lesions of the left colon is total-subtotal colectomy plus anastomosis between the ileum and rectum or sigmoid colon. The tumor can be resected in a single session and stoma complications can be avoided.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations